Elite Kenyan endurance runners are hydrated day-to-day with ad libitum fluid intake - Fudge, B. W.; Easton, C.; Kingsmore, D.; Kiplamai, F. K.; Onywera, V. O.; Westerterp, K. R.; Kayser, B.; Noakes, T. D.; Pitsiladis, Y. P. (Medicine & Science in Sports & Exercise, 2008)
Previous studies of elite Kenyan endurance runners reported that athletes did not consume liquids before or during training and infrequently consumed modest amounts of liquids after training that contributed to low daily fluid intake.